A dinâmica do comércio de autosserviço do varejo alimentar e a expansão das lojas de vizinhança na cidade de Uberaba (MG) - Silva, Mauro Beirigo da (2011)
Scientific knowledge in geography, economic and commercial dynamics have changed not only the relationship between the land, architecture and landscape of the cities, but also influences the behavior of citizens looking for self-service for their survival. In recent decades, due to changes in economic and socio-cultural, and technological advancement, communication speed and the transport system, it became possible to observe a commercial and geo-economic shift away from city centers, especially the so-called cities averages for the districts. Uberaba, located in the Mesorregião do Triângulo Mineiro e alto Paranaíba, has a population, according to IBGE, more than 2955000 inhabitants with a gross national product of R$ 6,221 billion reais. In town, we can see that this migration has transformed the business dynamics of the urban territory with the creation of new shopping centers, from the inclusion of self-service large surfaces, especially in the retail supermarket sector and even wholesale. In this sense, this research aims to understand the dynamics of retail self-service retail food Uberaba (MG) and the expansion of trade in the city neighborhood stores. Results reveal that there has been a devolution of supermarkets for the neighborhoods of Uberaba, including national networks, transnational, regional and local. In addition, strategies were self-serving survival of the neighborhood in the city, as wide variety of product mix, advertising and direct interaction between management and consumers, as well as loyalty cards, combined with attractive price and good service, which has shown be effective in maintaining old customers and win new.